Controllable design of nanoworm-like nickel sulfides for efficient electrochemical water splitting in alkaline media. (December 2020) - Chen, Z.; Ibrahim, I.; Hao, D.; Liu, X.; Wu, L.; Wei, W.; Su, D.; Ni, B.-J.
Abstract: Developing cost-effective electrocatalysts for electrochemical water splitting (EWS) is appealing and challenging for sustainable water electrolysis. Currently, nickel sulfides are considered as promising candidates for EWS due to their low cost and high catalytic activity. However, the facile design of nickel sulfides with high catalytic performance is still highly demanded. In this study, we have developed a one-step solvothermal strategy to construct nickel sulfides as efficient water splitting catalysts. By taking advantage of the small size, abundant active sites, large electrochemical surface area, and good conductivity, the nanoworm-like nickel sulfides (NiS-NW/Ni foam [NF]) exhibit better oxygen evolution reaction performance (a low overpotential of 279 mV to achieve 100 mA cm −2, Tafel slope of 38.44 mV dce −1 ) than the nanoplate-like analogs, as well as most of reported nickel sulfide–based electrocatalysts. In addition, the NiS-NW/NF directly used as bifunctional electrodes for overall water splitting requires a low voltage of 1.563 V to attain a current density of 10 mA cm −2 with good long-term durability. This work provides a facile strategy for the design of efficient nickel sulfide-based electrocatalysts for energy conversion applications. Graphical abstract: The nanoworm-like nickel sulfides developed by a one-step solvothermal strategy exhibit great performance for overall electrochemical water splitting, and a low voltage of 1.563 V is required to attain a current density of 10 mA cm −2 in a two-electrode electrolyzer. Image 1 Highlights: The nanoworm (NW)-like nickel sulfides (NiS) were designed by a facile solvothermal process. The solvothermal precursors govern the nanostructure of NiS. The NW-like NiS outperforms the nanoplate-like counterpart for water splitting. The NW-like NiS exhibits good activity and stability for overall water splitting.